Study of Thick Gaseous Electron Multipliers Gain Stability and Some Influencing Factors - Zhou, Xiao-Kang; Liu, Qian; Chen, Shi; Huang, Wen-Qian; Wang, Bin-Long; Zhang, Yong-Dong; Ge, Dong-Sheng; Liu, Hong-Bang; Zheng, Yang-Heng; Xie, Yi-Gang; Dong, Yang; Zhang, Qiang; et al. (Chinese physics letters, 2014)
The working stability of thinner-thick gaseous electron multipliers （THGEMs）, which have been developed by the University of the Chinese Academy of Sciences and the Second Academy of China＇s Aerospace Science and Industry Corporation, is studied with an 8 keV x-ray on a Cu target. Gains of about 103–104 are achieved with a single board in Ar：iC4H10 （97：3）. Environmental factors, such as pressure, temperature and humidity are considered. The thinner-THGEMs are shown to perform stably over two months of studies.